Role-playing in cognitive behavioral supervision - Prasko, Jan; Vanek, Jakub; Ociskova, Marie; Krone, Ilona; Slepecky, Milos; Abeltina, Marija; Burkauskas, Julius; Grambal, Aleš; Bagdonaviciene, Lina (Neuro-endocrinology letters, 2023)
Role-play helps the supervisor present a moment of therapy, and reflect on what has happened to the therapist to the patient and further model the therapeutic skills. Usually, the supervisor or other supervisees (in group supervision) play the patient, and the therapist plays a significant moment in the psychotherapeutic session. Supervisors or supervisees in group supervision can play the patient in different situations, and can also reverse roles when the therapist plays their patient, and the supervisor plays the therapist. Before role-playing, there is a need to set a specific goal. Playing roles in supervision can focus on (a) conceptualizing the case; (b) assessing and optimizing therapeutic strategies; (c) a better understanding of the therapeutic relationship. A specific goal needs to be set before role-playing. The technique can focus on (a) case conceptualization; (b) assessment and optimization therapeutic strategies; (c) a better understanding of the therapeutic relationship. A variety of approaches can be used for role-playings, such as pattern learning, modelling, chaining, encouragement and feedback, or psychodrama techniques such as monologue, an empty chair, role change, alter-ego, using multiple chairs or toys.
Keywords: Learning; Cognition; kognice; lidé; učení; motivace; Motivation; Humans